Dispersion liquid for grinding
Patent Information
- Application Number
- JP2025506221
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-10-13
- Filing Date
- 2024-10-07
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-10-07
AI Technical Summary
The hardness and brittleness of materials such as SiC make it difficult to deal with during processing, resulting in low production efficiency and high cost. The existing CMP technology uses diamond particles or colloidal silica particles for multi-stage long-term polishing, which consumes a large amount of consumables and equipment, resulting in high costs.
A polishing dispersion containing specific zirconium oxide particles has a grain diameter ratio of between 0.50 and 0.95 when polishing the dispersion liquid is used, and polishing rate and surface smoothness can be improved.
Efficient polishing treatment is achieved, which significantly improves the surface smoothness and polishing rate of materials such as SiC, and reduces the time and cost of the polishing process.
Abstract
Description
Polishing dispersion liquid
[0001] The present invention relates to a polishing dispersion containing zirconium oxide.
[0002] Polishing is widely used in the microelectronics industry. Materials such as silicon carbide (SiC) boast a dielectric breakdown strength 10 times that of silicon and a band gap three times that of silicon. They have also attracted attention in recent years as power semiconductors with excellent high-temperature and energy-saving properties. For similar reasons, gallium nitride (GaN), diamond, and sapphire are also attracting attention and are being actively developed. High-yield production of high-performance devices requires atomic-level flatness and smoothness of substrates. However, these substrates are harder and more brittle than silicon, and are chemically more stable and difficult to process, resulting in low productivity and rising substrate processing costs. Traditionally, after slicing the crystal, multi-stage, long-term polishing is performed using chemical mechanical polishing (CMP) with diamond or colloidal silica particles. However, this process incurs significant costs in terms of consumables and equipment, resulting in costs several times higher than those for silicon substrates. Reducing this processing cost is strongly required for the widespread use of power semiconductors. Several dispersions using zirconium oxide as an abrasive have also been proposed.
[0003] For example, Patent Document 1 discloses a polishing slurry that contains 1 to 20 mass % of monoclinic zirconium oxide having a crystallite size of 10 to 1,000 nm and an average particle size of 30 to 2,000 nm, and further contains a carboxylic acid having three or more carboxy groups in the molecule and a quaternary alkyl ammonium hydroxide, and has a pH of 9 to 12.
[0004] Patent Document 2 discloses a polishing powder containing zirconium oxide particles, characterized in that the zirconium oxide particles have crystallite sizes of 330 Å or more, calculated based on the diffracted X-ray intensities at 2θ of around 28.0° and 31.0° as measured by powder X-ray diffraction, and the zirconium oxide particles have an average primary particle size of 0.2 μm or more.
[0005] Patent Document 3 discloses a slurry for chemical mechanical polishing (CMP) containing an aqueous liquid carrier, a transition metal oxy-compound selected from oxy-nitrates, oxy-chlorides, oxy-sulfates, oxy-carbonates, and C2 to C10 oxy-alkanoates, and a per-based oxidizing agent, and discloses a SiC abrasive slurry using zirconia particles.
[0006] Patent Document 4 discloses a method for producing a polishing composition containing zirconium oxide sol, the method comprising the steps of: calcining a zirconium compound having a d50 (where d50 represents a particle size where the number of particles having this particle size or less accounts for 50% of the total number of particles) of 5 to 25 μm and a d99 (where d99 represents a particle size where the number of particles having this particle size or less accounts for 99% of the total number of particles) of 60 μm or less when a slurry of the zirconium compound is measured by a laser diffraction method, at a temperature range of 400 to 1000° C.; and wet-pulverizing the obtained zirconium oxide powder in an aqueous medium until the d50 of the zirconium oxide particles reaches 80 to 150 nm and the d99 of the zirconium oxide particles reaches 150 to 500 nm when the zirconium oxide slurry is measured by a laser diffraction method.
[0007] JP 2006-324639 A, WO 2012 / 169515, JP 2023-512216 A, WO 2006 / 123562
[0008] However, since SiC and the like are hard and difficult to process, further improvements in production efficiency and the like are required.
[0009] The present invention relates to a polishing dispersion that has an excellent polishing rate and excellent surface smoothness after polishing. The present invention also provides a method for producing the polishing dispersion, a method for improving the polishing rate, a method for reducing surface roughness Ra, and a polishing powder.
[0010] The present invention relates to the following items [1] to [5]: [1] A polishing dispersion containing zirconium oxide having a monoclinic phase and a crystallite size ratio ((-111) plane / (111) plane) of 0.50 to 0.95 between the monoclinic (-111) plane and the monoclinic (111) plane, and a polishing aid. [2] A method for producing a polishing dispersion containing zirconium oxide and a polishing aid, the method comprising the step of preparing a dispersion using zirconium oxide having a monoclinic phase and a crystallite size ratio ((-111) plane / (111) plane) of 0.50 to 0.95 between the monoclinic (-111) plane and the monoclinic (111) plane, and a polishing aid. [3] A method for improving the removal rate, comprising polishing using zirconium oxide containing a monoclinic phase and having a crystallite size ratio ((-111) plane / (111) plane) of 0.50 to 0.95 between the monoclinic (-111) plane and the monoclinic (111) plane, and a polishing aid. [4] A method for reducing surface roughness Ra, comprising polishing using zirconium oxide containing a monoclinic phase and having a crystallite size ratio ((-111) plane / (111) plane) of 0.50 to 0.95 between the monoclinic (-111) plane and the monoclinic (111) plane, and a polishing aid. [5] A polishing powder comprising zirconium oxide powder containing a monoclinic phase and having a crystallite size ratio ((-111) plane / (111) plane) of 0.50 to 0.95 between the monoclinic (-111) plane and the monoclinic (111) plane.
[0011] According to the present invention, a polishing dispersion having an excellent polishing rate and excellent surface smoothness after polishing can be provided. Also, a method for producing the polishing dispersion, a method for improving the polishing rate, a method for reducing the surface roughness Ra, and a polishing powder can be provided. By achieving both a high polishing rate and low surface roughness, the conventional polishing process for SiC and the like can be significantly shortened.
[0012] It has been known that the removal rate of a polishing powder is generally proportional to the average particle size of the polishing powder. Meanwhile, it is generally believed that the smallest possible average particle size of the abrasive is desirable to obtain a polished surface with low surface roughness and minimal surface defects. In response to this, the present inventors have investigated the above-mentioned problems and have newly discovered that the above-mentioned object can be achieved by using a polishing powder containing specific zirconium oxide particles. More specifically, they have newly discovered that by using zirconium oxide particles as abrasives with a crystallite size ratio of the monoclinic (-111) plane to the monoclinic (111) plane ((-111) plane / (111) plane) of 0.50 to 0.95, both the removal rate and the surface smoothness after polishing can be improved. Among these, zirconia oxide particles containing a tetragonal phase at a volume fraction of 2.0 to 90.0% and with each crystallite size of 2.0 to 100.0 nm are exemplified as a preferred embodiment. All of these can be synthesized in a wet environment using a process that does not require high-temperature treatment. While the mechanism is unclear, it is presumed to be due to the following reasons. When the ratio of the crystallite diameters of the monoclinic (-111) plane to the monoclinic (111) plane ((-111) plane / (111) plane) is close to 1.0, the monoclinic crystals are presumed to have grown uniformly without directionality, i.e., to have a shape close to spherical. On the other hand, as the ratio of the crystallite diameters of the monoclinic (-111) plane to the monoclinic (111) plane ((-111) plane / (111) plane) becomes smaller than 1, the monoclinic crystals are presumed to become rectangular or rod-shaped with a larger aspect ratio. The latter rectangular or rod-shaped crystals are more difficult to rotate than the former spherical crystals, resulting in increased frictional resistance with the polished surface, which is thought to have the effect of improving the polishing rate of the substrate. Furthermore, rectangular and rod-shaped particles are thought to be superior to spherical particles in terms of smoothness (reducing surface roughness) because they form line or surface contact when colliding with the surface to be polished, dispersing the impact.
[0013] The polishing dispersion of the present invention contains zirconium oxide containing a monoclinic phase and having a crystallite size ratio of the monoclinic (-111) plane to the monoclinic (111) plane ((-111) plane / (111) plane) of 0.50 to 0.95, and a polishing aid.
[0014] The zirconium oxide of the present invention generally refers to one containing a few percent of hafnium oxide as an unavoidable impurity, generally 1.0 to 3.0%, but may also be one that has been purified to remove hafnium oxide. The zirconium oxide may also be stabilized zirconium oxide, in which case calcium, magnesium, yttrium, cerium, and other rare earth elements may be solid-solubilized. Other elements that are solid-solubilized in zirconium oxide may also be included. Zirconium oxide may also be composite particles of other oxides to form a single particle. Zirconium oxide functions as an abrasive grain, and by satisfying the above requirements, a high polishing rate and low surface roughness can be achieved. The above requirements are determined by powder X-ray diffraction measurement of a powder obtained by drying the polishing dispersion of the present invention and analysis of the diffraction chart obtained by the measurement. Detailed conditions for the powder X-ray diffraction measurement and analysis will be described later.
[0015] Known crystalline phases of zirconium oxide include monoclinic, tetragonal, and cubic phases, but the zirconium oxide according to the present invention contains at least the monoclinic phase. From the viewpoints of polishing rate and smoothness, the monoclinic phase ratio in the zirconium oxide according to the present invention is preferably 10 to 100%, more preferably 10 to 90%, even more preferably 20 to 80%, and even more preferably 30 to 70% by volume. The crystalline phase content is measured by the method described in the Examples below.
[0016] The ratio of the crystallite size of the monoclinic (-111) plane to the monoclinic (111) plane in the monoclinic phase ((-111) plane / (111) plane) is 0.50 to 0.95, preferably 0.52 to 0.93, more preferably 0.54 to 0.91, even more preferably 0.56 to 0.89, and even more preferably 0.58 to 0.87, from the viewpoints of polishing rate and smoothness. The crystallite size is measured by the method described in the Examples below.
[0017] From the viewpoint of smoothness, the zirconium oxide according to the present invention preferably further contains a tetragonal phase. From the viewpoint of smoothness, the tetragonal phase ratio in the zirconium oxide according to the present invention is preferably 2.0 to 90.0%, more preferably 3.0 to 80.0%, even more preferably 4.0 to 70.0%, and still more preferably 5.0 to 60.0% in volume fraction.
[0018] In the embodiment containing the tetragonal phase, the ratio of the crystallite size of the monoclinic (−111) plane to the tetragonal (101) plane ((−111) plane / (101) plane) is preferably 0.30 to 1.20, more preferably 0.35 to 1.15, even more preferably 0.40 to 1.10, and still more preferably 0.45 to 1.05, from the viewpoints of polishing rate and smoothness.
[0019] The mechanism by which the above-mentioned tetragonal phase-containing embodiment exhibits particularly excellent smoothness is unclear, but is presumed to be due to the following reasons. The tetragonal phase has the property of undergoing a phase transition to a monoclinic phase under pressure, which is accompanied by a volume expansion of several percent. Presumably, when exposed to pressure at the interface between the polishing pad and the polished surface, at least a portion of the tetragonal phase transitions to the monoclinic phase, and the volume expansion at that time causes the aggregation of crystallites to break apart, loosening the aggregation and thereby alleviating the above-mentioned exposed pressure. As a result, it is presumed that the instantaneous overpressure on the polished surface caused by the polishing grains, which would occur intermittently during polishing, is suppressed, leading to a reduction in surface roughness. Furthermore, it is presumed that this tetragonal phase transition effect is more efficiently manifested when the crystallite size ratio between the monoclinic (-111) plane and the tetragonal (101) plane ((-111) plane / (101) plane) is 0.30 to 1.20.
[0020] The method for adjusting the crystallite size ratio of the monoclinic (-111) plane to the monoclinic (111) plane ((-111) plane / (111) plane) in the monoclinic phase and the crystallite size ratio of the monoclinic (-111) plane to the tetragonal (101) plane ((-111) plane / (101) plane) is not limited, but adjustments will be explained in the manufacturing mode of zirconium oxide sol described in the Examples below. The manufacturing method of zirconium oxide sol of this embodiment includes step A, in which aqueous ammonia is added dropwise to an aqueous zirconium oxychloride solution to neutralize it, and step B, in which the zirconium hydroxide obtained in step A is heat-aged under acidic conditions. In step A, aqueous ammonia is added dropwise multiple times, for example, in two stages. In the first stage, NH 3 In the first stage, an equimolar amount of aqueous ammonia is added dropwise to the zirconium oxychloride solution in a ratio of Zr to the total amount of aqueous ammonia, followed by a predetermined period of time. The second stage involves adding aqueous ammonia dropwise and then maintaining the solution for a predetermined period of time. The higher the temperature of the aqueous zirconium oxychloride solution, the larger the crystallite size, and the higher the crystallite size ratio ((-111) / (111)) between the monoclinic (-111) plane and the monoclinic (111) plane. By lengthening the retention time in the first stage, the crystallite size ratio ((-111) / (111)) can be lowered. By lengthening the retention time in the second stage, the tetragonal ratio and the crystallite size ratio ((-111) / (101)) between the monoclinic (-111) plane and the tetragonal (101) plane can be lowered.
[0021] The crystallite diameter of each crystal plane (monoclinic (-111) plane, monoclinic (111) plane, tetragonal (101) plane, and cubic (111) plane) of zirconium oxide according to the present invention is preferably 2.0 to 100.0 nm, more preferably 3.0 to 80.0 nm, even more preferably 4.0 to 60.0 nm, and even more preferably 5.0 to 40.0 nm, from the viewpoints of polishing rate and smoothness. Regarding the crystal planes of zirconium oxide, the monoclinic (-111) plane may be expressed as m(-111), the monoclinic (111) plane as m(111), the tetragonal (101) plane as t(101), and the cubic (111) plane as c(111). Furthermore, since the t(101) and c(111) planes have the same peak position in powder X-ray diffraction measurement, they are not distinguished and are treated as having the same meaning. That is, in the present invention, the t(101) and c(111) peaks are treated as the t(101) peak.
[0022] The median particle diameter (particle diameter D 50 From the viewpoint of polishing rate and smoothness, the median diameter (particle diameter D 50 ) is measured by the method described in the Examples below. As described above, the function of the present invention is considered to be mainly due to the properties related to the crystallites of zirconium oxide, and therefore the aggregate particle size is not particularly limited.
[0023] The content of zirconium oxide in the polishing dispersion of the present invention can be appropriately selected depending on the object to be polished and the polishing conditions, but is usually 0.1 to 20% by mass, preferably 1 to 15% by mass. Furthermore, abrasive particles other than zirconium oxide may coexist as long as the polishing performance of the present invention is not impaired. Examples of abrasive particles other than zirconium oxide include known inorganic particles, organic particles, and organic-inorganic composite particles, such as oxide particles such as silica particles, alumina particles, cerium oxide particles, chromium oxide particles, titanium dioxide particles, magnesium oxide particles, manganese dioxide particles, zinc oxide particles, and iron oxide particles; nitride particles such as silicon nitride particles and boron nitride particles; carbide particles such as silicon carbide particles, green silicon carbide (GC) particles, and boron carbide particles; diamond particles; carbonates such as calcium carbonate and barium carbonate; and the like.
[0024] In the above embodiment in which abrasive grains other than zirconium oxide are contained, the concentration of the abrasive grains other than zirconium oxide is preferably 10% by mass or less, more preferably 5% by mass or less, based on the total abrasive grain concentration.
[0025] The grinding aid of the present invention is a component that enhances the effect of polishing, and is preferably water-soluble.As the grinding aid, peroxides such as hydrogen peroxide; nitrate compounds such as iron nitrate, silver nitrate, aluminum nitrate, and its complex cerium ammonium nitrate; persulfates such as potassium peroxomonosulfate, peroxodisulfate, and its salts, persulfate compounds such as ammonium persulfate, potassium persulfate; chlorine compounds such as chloric acid, its salts, perchloric acid, and its salts, potassium perchlorate; bromine compounds such as bromic acid, its salts, potassium bromate; iodic acid, its salts, ammonium iodate; periodic acid, its salts, sodium periodate, potassium periodate, and other iodine compounds; iron acids such as ferric acid, its salts, potassium ferrate; permanganic acids such as permanganic acid, its salts, sodium permanganate, potassium permanganate; chromic acids such as chromic acid, its salts, potassium chromate, potassium dichromate; Examples of suitable oxidizing agents include vanadic acids such as vanadic acid and its salts, ammonium vanadate, sodium vanadate, sodium metavanadate, and potassium vanadate; ruthenic acids such as perruthenic acid and its salts; molybdic acids such as molybdic acid and its salts, ammonium molybdate and disodium molybdate; rhenic acids such as perrhenium and its salts; and tungstic acids such as tungstic acid and its salts, disodium tungstate; and these oxidizing agents can be used alone or in combination of two or more. Among these, from the viewpoint of polishing efficiency, oxidizing agents are preferred, and potassium permanganate, sodium permanganate, periodic acid, potassium persulfate, and aqueous hydrogen peroxide are particularly preferred.
[0026] The content of the polishing aid in the polishing dispersion of the present invention can be appropriately selected depending on the object to be polished and the polishing conditions, but is usually 0.1 to 20.0 mass %, preferably 1.0 to 10.0 mass %.
[0027] The dispersion medium of the polishing dispersion of the present invention is not limited as long as it can ensure polishing performance, but is usually water, and ion-exchanged water, pure water, ultrapure water, distilled water, etc. can also be used. If necessary, it may further contain an organic solvent (lower alcohol, lower ketone, etc.) that can be uniformly mixed with water. The content of water in the dispersion medium is preferably 90% by volume or more, more preferably 95% by volume or more, and even more preferably 100% by volume.
[0028] The pH of the polishing dispersion of the present invention is not limited and can be adjusted as needed to adjust the potential between the abrasive grains and the surface to be polished. For example, the pH can be 0.5 to 13.5, 1.0 to 13.0, or 1.5 to 12.5. The pH can be adjusted by adding a common acid (hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, acetic acid, etc.) or a common base (sodium hydroxide, ammonia, amine, etc.) to the polishing dispersion.
[0029] The polishing dispersion of the present invention may optionally contain various additives other than those described above. Examples of known additives include chelating agents, thickeners, dispersants, surface protective agents, wetting agents, pH adjusters, surfactants, organic acids, organic acid salts, inorganic acids, inorganic acid salts, rust inhibitors, preservatives, and antifungal agents. The type and concentration of these optional additives are not limited as long as they ensure the polishing performance of the present invention.
[0030] The polishing dispersion of the present invention may contain impurities such as inorganic ions such as nitrate ions, chloride ions, and sulfate ions, metal ions such as sodium, potassium, iron, and titanium, and organic ions such as acetate ions and tetramethylammonium ions, but this is not a particular problem as long as the polishing performance of the present invention is ensured.
[0031] The polishing dispersion of the present invention has an excellent polishing rate and provides excellent surface smoothness after polishing, and is therefore suitable for polishing substrates such as Si, SiC, GaN, and sapphire, oxide films, and metal films such as W and Cu, and is particularly suitable for polishing SiC wafers. Therefore, the present invention also provides a method for improving the polishing rate and reducing the surface roughness Ra by polishing using zirconium oxide containing a monoclinic phase and having a crystallite size ratio ((-111) plane / (111) plane) of 0.50 to 0.95 between the monoclinic (-111) plane and the monoclinic (111) plane, and a polishing aid. Here, polishing using zirconium oxide and a polishing aid includes not only an embodiment in which a polishing dispersion in which zirconium oxide and a polishing aid are premixed is used, but also an embodiment in which they are used separately for polishing.
[0032] Regarding the polishing performance of the polishing dispersion of the present invention, for example, the polishing rate under the conditions of the examples described later (Si surface polishing of SiC wafer) is preferably 0.5 μm / h or more, more preferably 0.6 μm / h or more, and even more preferably 0.7 μm / h or more. As long as the surface roughness does not exceed a certain level, the higher the polishing rate, the better, but it can be, for example, 5 μm / h or less, 3 μm / h or less, etc.
[0033] The smoothness after polishing using the polishing dispersion of the present invention, for example, under the conditions of the examples described later (polishing the Si face of a SiC wafer), is preferably 1.0 Å or less, more preferably 0.9 Å or less, and even more preferably 0.8 Å or less. The smaller the surface roughness Ra of the polished surface, the better, but it can be, for example, 0.1 Å or more, 0.2 Å or more, etc.
[0034] The method for producing the polishing dispersion of the present invention is not particularly limited, but an example includes a production method comprising the step of preparing a dispersion using zirconium oxide containing a monoclinic phase and having a crystallite size ratio ((-111) / (111)) of 0.50 to 0.95 between the monoclinic (-111) plane and the monoclinic (111) plane, and a polishing aid. That is, the polishing dispersion of the present invention can be produced by mixing a predetermined zirconium oxide, a polishing aid, a dispersion medium, and optional additives. The method and order of mixing these components are not particularly limited as long as the physical properties of the polishing dispersion are achieved. An example of a mixing procedure for producing a polishing dispersion is shown below. In the first step, a predetermined zirconium oxide is dispersed as a dispersoid in a dispersion medium. If necessary, a pulverization process using a bead mill or the like may be performed. The concentration of zirconium oxide can be appropriately selected depending on the object to be polished and the polishing conditions. In the first step, an acid, a base, a dispersant, or the like may be added to aid in the dispersion of zirconium oxide. In the particle size distribution measurement of the dispersion obtained in the first step by dynamic light scattering, 50 The first step can be considered complete when the value of is 2.0 to 5000.0 nm. Next, in the second step, an oxidizing agent (polishing aid) such as potassium permanganate or hydrogen peroxide, and, if necessary, abrasive grains other than zirconium oxide, a common acid (hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, acetic acid, etc.) primarily intended for pH adjustment, a common base (sodium hydroxide, ammonia, amine, etc.), a dispersant, and other chemicals of interest, etc., can be added to the dispersion obtained in the first step to produce a polishing dispersion.
[0035] The polishing powder of the present invention contains the specified zirconium oxide powder described above, i.e., zirconium oxide powder containing a monoclinic phase and having a crystallite size ratio of the monoclinic (-111) plane to the monoclinic (111) plane ((-111) plane / (111) plane) of 0.50 to 0.95, and the tetragonal phase ratio, etc. are the same as those described above.
[0036] The zirconium oxide powder according to the polishing powder of the present invention can be produced by a wet method, and has a purity of preferably 97 to 100 mass %, more preferably 98 to 100 mass %, and even more preferably 99 to 100 mass %.
[0037] The average secondary particle size of the zirconium oxide powder according to the polishing powder of the present invention is preferably 0.002 to 5 μm, more preferably 0.003 to 1 μm, even more preferably 0.004 to 0.5 μm, and even more preferably 0.005 to 0.1 μm, from the viewpoints of polishing rate and smoothness. The average secondary particle size is measured by a general dynamic light scattering method.
[0038] The specific surface area of the zirconium oxide powder according to the polishing powder of the present invention is preferably 20 to 200 m from the viewpoint of polishing rate and smoothness. 2 / g, more preferably 30 to 180 m 2 / g, more preferably 40 to 170 m 2 / g, more preferably 50 to 160 m 2 The specific surface area is measured by a general BET method using nitrogen adsorption.
[0039] The content of zirconium oxide powder in the polishing powder of the present invention is preferably 97.0 to 99.9 mass %, more preferably 98.0 to 99.5 mass %, and even more preferably 98.5 to 99.0 mass %.
[0040] The polishing powder of the present invention may optionally contain abrasive grains other than the zirconium oxide, a surface modifier, and the like.
[0041] EXAMPLES The present invention will be specifically explained below with reference to examples and comparative examples, but the present invention is not limited to these.
[0042] [Particle diameter D 50 Measurement] The polishing dispersion obtained in each Example and Comparative Example was 2 The solution was diluted to 1.0 mass % in terms of the total mass of the solution, and then placed in a dynamic light scattering particle size distribution analyzer ("Zetasizer Nano ZS" manufactured by Malvern Panalytical) to measure the particle diameter D 50 (volume frequency distribution standard) was measured. <Measurement conditions> Measurement temperature: 25°C Scattering angle: 173° Dispersoid: ZrO 2 Dispersion medium: Water Cell: Genuine disposable cell Number of repetitions: 3 (D 50 is the average of three measurements)
[0043] [Powder X-ray Diffraction Measurement and Analysis] The polishing dispersions obtained in each Example and Comparative Example were dried at 100°C using an X-ray diffractometer ("RINT2500" manufactured by Rigaku) to obtain X-ray diffraction charts. The charts were analyzed in the 2θ = 20 to 40° range using Powder XRD, SmartLab Studio II (RIGAKU), and the crystallite size and crystalline phase ratio were calculated. For this calculation, the three peaks with their tops located in the ranges of 27.5 to 28.5°, 29.5 to 30.5°, and 31.0 to 32.0° on the diffraction chart were targeted. The range from 27.5 to 28.5° is attributed to m(-111), the range from 29.5 to 30.5° to t(101) or c(111), and the range from 31.0 to 32.0° to m(111). As mentioned above, the t(101) and c(111) peaks are treated as the t(101) peak. Even if the peak angle falls outside the above range or the peak is split due to a change in the lattice constant caused by the solid solution of other elements in zirconium oxide, the peak can be used in this analysis as long as it is appropriate to attribute it to the above crystal plane. The tetragonal phase ratio was calculated using the following formula based on the diffraction peak intensity I of each crystal plane obtained in the above analysis. The monoclinic phase ratio can also be calculated in a similar manner.
[0044] [Powder X-ray diffraction analysis details] After loading powder X-ray diffraction measurement data into Powder XRD software in SmartLab Studio II, peak processing is performed. Peak profiling conditions are set as follows: Peak search: Check box ON Preprocessing: Customize Method: Second-order differential method σ cut value: 3 (adjust between 0.5 and 3 if no clearly visible peaks are detected) Profile fitting: Check box ON Peak shape: Divided pseudo-Voigt function Background type: B-spline Fitting conditions: Automatic Refine background: Check box ON To calculate the crystallite size and crystallite size ratio, use the value displayed in the Crystallite size (Å) column displayed on the Peak List tab (values in parentheses are ignored). To calculate the tetragonal crystal ratio, use the value displayed in the Integrated intensity (count°) column displayed on the Peak List tab (values in parentheses are ignored). Tetragonal phase ratio (%) = It(101) / {It(101)+Im(-111)+Im(111)} ×100 Measurement device: X-ray diffraction device (Rigaku, RINT2500) Source: CuKα source Tube voltage: 50kV Tube current: 300mA Scanning accuracy: 2Θ=10~50° Scanning speed: 1° / min
[0045] [Polishing Performance Evaluation] SiC wafers were polished using the polishing dispersions of Examples and Comparative Examples, and the polishing rate and surface roughness Ra of the polished surface were measured. The polishing rate was measured by measuring the weight of the substrate before and after polishing and calculating the difference. The surface roughness Ra of the polished surface of the object to be polished after polishing was measured under conditions where the viewing angle was 5.0 μm × 5.0 μm. The surface roughness Ra was measured using an atomic force microscope (AFM) (Dimension Edge, manufactured by Bruker) in accordance with JIS B 0601-2001. The polishing conditions were as follows: Substrate (object to be polished): 4H-SiC wafer, 4 inches, Si surface, off-axis angle 4 degrees, non-doped (surface roughness Ra approx. 1 Å) Polishing device: Single-sided polishing device (ENGIS EJ-380N) Polishing pad: SUBA600 (Nitta DuPont) Polishing load: 280 g / cm2 Rotation speed of the surface plate: 80 rpm (linear velocity: 9.5 m / min) Polishing time: 2 hours Supply rate of the polishing composition: 10 mL / min Measurement area of the object to be polished: 5.0 μm×5.0 μm (surface roughness)
[0046] [Evaluation of surface defects] After polishing the object to be polished, surface defects were measured at five random points within a 1.0 x 1.0 mm field of view using a polarizing microscope (Keyence, VHX-7100), and the average value was used to evaluate the surface defects according to the following evaluation criteria: (Evaluation criteria) ◎: Not detected ○: More than 0 and 1 or less △: More than 1 and 2 or less ×: More than 2
[0047] (Example 1) An aqueous solution of zirconium oxychloride (ZrO 2 Neutralization was carried out in two stages by dropwise addition of ammonia water to 8,000 g of ammonia water (10% by mass equivalent). In the first stage, 1,104 g of ammonia water (10% by mass) adjusted to 25°C was added dropwise over 10 minutes. The number of liquid delivery tubes and the drop rate were adjusted so that the volume of the ammonia water droplets was in the range of 0.1 to 0.5 ml. Stirring was then continued for 60 minutes. In the second stage, 9,936 g of ammonia water (10% by mass) adjusted to 25°C was added dropwise over 30 minutes, and stirring was continued for 10 minutes to obtain a zirconium hydroxide precipitate. The temperature of the aqueous zirconium oxychloride solution was adjusted to be maintained within ±5°C of the initial temperature during the dropwise addition of ammonia water and during stirring after the dropwise addition. The zirconium hydroxide was filtered off and dispersed again in ion-exchanged water, and a washing procedure was repeated. This procedure was continued until the Cl concentration was 0.01% or less. The concentration of zirconium hydroxide after washing was ZrO 2 The zirconium hydroxide thus obtained was converted to a sol of 24.0% by mass. 3,328 g of the resulting zirconium hydroxide was mixed with 4,448 g of ion-exchanged water and 224 g of nitric acid (60% by mass), and the resulting slurry was placed in a separable flask and stirred under reflux at 100°C for 120 hours. The resulting zirconium oxide precursor was purified by ultrafiltration, yielding a zirconium oxide sol according to Example 1. The ZrO 2 The concentration is 20%, pH 3.3 and D 50The specific surface area of the powder obtained by drying the sol was 175 m 2 / g. Next, 952 g of ion-exchanged water and 48 g of potassium permanganate were added to 3,000 g of this zirconium oxide sol and stirred for 30 minutes to obtain a polishing dispersion. Powder X-ray diffraction measurement and analysis, as well as polishing performance evaluation, are shown in Table 1 together with other examples and comparative examples.
[0048] (Example 2) An aqueous solution of zirconium oxychloride (ZrO 2 Zirconium hydroxide was obtained in the same manner as in Example 1, except that 8,000 g of sintered zirconium hydroxide (equivalent to 10 mass %) was used. The concentration of zirconium hydroxide after washing was 2 The zirconium oxide sol was obtained in the same manner as in Example 1, except that 3512 g of the obtained zirconium hydroxide was used in combination with 4264 g of ion-exchanged water. 2 The concentration is 20%, pH 3.1 and D 50 Next, a polishing dispersion was obtained in the same manner as in Example 1 using this zirconium oxide sol.
[0049] (Example 3) An aqueous solution of zirconium oxychloride (ZrO 2 Zirconium hydroxide was obtained in the same manner as in Example 1, except that 8,000 g of sintered zirconium hydroxide (equivalent to 10 mass %) was used. The concentration of zirconium hydroxide after washing was 2 The zirconium oxide sol was obtained in the same manner as in Example 1, except that 4024 g of ion-exchanged water was used in addition to 3752 g of the obtained zirconium hydroxide. 2 The concentration is 20%, pH 3.4 and D 50 Next, a polishing dispersion was obtained in the same manner as in Example 1 using this zirconium oxide sol.
[0050] (Example 4) An aqueous solution of zirconium oxychloride (ZrO 2Zirconium hydroxide was obtained in the same manner as in Example 1, except that 8,000 g of aqueous ammonia (10% by mass, calculated as ZrO) was used, and in the second stage, 1,104 g of aqueous ammonia (10% by mass) adjusted to 25°C was added dropwise over 10 minutes, and then stirring was continued for 90 minutes. The concentration of zirconium hydroxide after washing was ZrO 2 The zirconium oxide sol was obtained in the same manner as in Example 1, except that 3,496 g of the obtained zirconium hydroxide was used in combination with 4,280 g of ion-exchanged water. 2 The concentration is 20%, pH 3.1 and D 50 Next, a polishing dispersion was obtained in the same manner as in Example 1 using this zirconium oxide sol.
[0051] (Example 5) An aqueous solution of zirconium oxychloride (ZrO 2 Zirconium hydroxide was obtained in the same manner as in Example 1, except that 8,000 g of aqueous ammonia (10% by mass, calculated as ZrO) was used, and in the second stage, 9,936 g of aqueous ammonia (10% by mass) adjusted to 25°C was added dropwise over 30 minutes, and then stirring was continued for 30 minutes. The concentration of zirconium hydroxide after washing was ZrO 2 The zirconium oxide sol was obtained in the same manner as in Example 1, except that 3,360 g of the obtained zirconium hydroxide was used in combination with 4,280 g of ion-exchanged water. 2 The concentration is 20%, pH 3.3 and D 50 Next, a polishing dispersion was obtained in the same manner as in Example 1 using this zirconium oxide sol.
[0052] (Example 6) An aqueous solution of zirconium oxychloride (ZrO 2 Zirconium hydroxide was obtained in the same manner as in Example 1, except that 1,000 g of aqueous ammonia (10% by mass, calculated as ZrO) was used, and in the second stage, 9,936 g of aqueous ammonia (10% by mass) adjusted to 25°C was added dropwise over 30 minutes, and stirring was continued for 60 minutes. The concentration of zirconium hydroxide after washing was ZrO 2 The zirconium oxide sol was obtained in the same manner as in Example 1, except that 3,448 g of the obtained zirconium hydroxide was used in combination with 4,328 g of ion-exchanged water.2 The concentration is 20%, pH 3.2 and D 50 Next, a polishing dispersion was obtained in the same manner as in Example 1 using this zirconium oxide sol.
[0053] (Example 7) An aqueous solution of zirconium oxychloride (ZrO 2 Zirconium hydroxide was obtained in the same manner as in Example 1, except that 1,000 g of aqueous ammonia (10% by mass, calculated as ZrO) was used, and in the second stage, 9,936 g of aqueous ammonia (10% by mass) adjusted to 25°C was added dropwise over 30 minutes, and stirring was continued for 120 minutes. The concentration of zirconium hydroxide after washing was ZrO 2 The zirconium oxide sol was obtained in the same manner as in Example 1, except that 3536 g of the obtained zirconium hydroxide was used in combination with 4240 g of ion-exchanged water. The ZrO2 concentration of the sol was 20%, pH 3.3, and D 50 Next, a polishing dispersion was obtained in the same manner as in Example 1 using this zirconium oxide sol.
[0054] (Comparative Example 1) Aqueous zirconium oxychloride solution (ZrO 2 1,000 g of ammonia water (10% by mass equivalent) was used, and 11,040 g of ammonia water (10% by mass) adjusted to 25°C was added dropwise over 40 minutes. The number of liquid delivery tubes and the dropping rate were adjusted so that the volume of the ammonia water droplets was in the range of 0.1 to 0.5 ml. Stirring was then continued for 10 minutes to obtain a precipitate of zirconium hydroxide. The concentration of zirconium hydroxide after washing was ZrO 2 The zirconium oxide sol was obtained in the same manner as in Example 1, except that 2816 g of the obtained zirconium hydroxide was used in combination with 4960 g of ion-exchanged water. 2 The concentration is 20%, pH 3.3 and D 50 Next, a polishing dispersion was obtained in the same manner as in Example 1 using this zirconium oxide sol.
[0055] Comparative Example 2 3,000 g of zirconium hydroxide obtained in the same manner as in Example 1 was packed into a cordierite sheath and fired in a batch-type electric furnace at 400°C for 10 hours to obtain zirconium oxide. A mixture of 600 g of the zirconium oxide, 1,400 g of ion-exchanged water, and 12.0 g of 60% nitric acid was pulverized in a bead mill using zirconium oxide pulverization media with a diameter of 0.3 mm to obtain a zirconium oxide sol. The ZrO 2 The concentration is 20%, pH 3.1 and D 50 Next, a polishing dispersion was obtained in the same manner as in Example 1 using this zirconium oxide sol.
[0056] Comparative Example 3 3,000 g of zirconium hydroxide obtained in the same manner as in Example 1 was packed into a cordierite sheath and fired in a batch electric furnace at 1,150°C for 10 hours to obtain zirconium oxide. A mixture of 600 g of the zirconium oxide, 1,400 g of ion-exchanged water, and 5.0 g of 60% nitric acid was pulverized in a bead mill using zirconium oxide pulverization media with a diameter of 0.3 mm to obtain a zirconium oxide sol. The ZrO 2 The concentration is 20%, pH 3.2 and D 50 The particle diameter was 236 nm. Next, a polishing dispersion was obtained in the same manner as in Example 1 using this zirconium oxide sol.
[0057]
[0058]
[0059] As shown in Tables 1 and 2, polishing using the polishing dispersions of each Example showed excellent polishing rates and surface smoothness after polishing. It can also be seen that each Example showed good polishing without any surface defects. Furthermore, Examples 5 to 7, which contained a tetragonal phase, all had lower surface roughness than Example 2, which did not contain a tetragonal phase, demonstrating superior smoothness.
[0060] The polishing dispersion and polishing powder of the present invention can be used for chemical mechanical polishing (CMP) of SiC wafers and the like, and can be utilized in semiconductor manufacturing processes and the like.
Claims
1. A polishing dispersion comprising zirconium oxide containing a monoclinic phase and having a crystallite size ratio of the monoclinic (-111) plane to the monoclinic (111) plane ((-111) plane / (111) plane) of 0.50 to 0.95, and a polishing aid.
2. The polishing dispersion according to claim 1, wherein the crystallite size of each crystal face of said zirconium oxide is 2.0 to 100.0 nm.
3. The polishing dispersion of claim 1, wherein said zirconium oxide further contains a tetragonal phase.
4. The polishing dispersion according to claim 3, wherein the content of the tetragonal phase in said zirconium oxide is 2.0 to 90.0% by volume.
5. The polishing dispersion according to claim 3, wherein the ratio of crystallite size between the monoclinic (-111) plane and the tetragonal (101) plane in said zirconium oxide ((-111) plane / (101) plane) is 0.30 to 1.
20.
6. The polishing dispersion according to claim 1, wherein the polishing aid comprises one or more selected from the group consisting of peroxides, nitric acid compounds, persulfuric acid compounds, chlorine compounds, bromine compounds, iodine compounds, ferric acids, permanganic acids, chromic acids, vanadic acids, ruthenic acids, molybdic acids, rhenic acids, and tungstic acids.
7. The polishing dispersion according to claim 1, which is used for polishing a SiC wafer.
8. A method for producing a dispersion for polishing containing zirconium oxide and a polishing aid, comprising the step of preparing a dispersion using zirconium oxide containing a monoclinic phase and having a crystallite size ratio between the monoclinic (-111) plane and the monoclinic (111) plane ((-111) plane / (111) plane) of 0.50 to 0.95, and a polishing aid.
9. A method for improving the polishing rate, comprising polishing using zirconium oxide containing a monoclinic phase and having a crystallite size ratio between the monoclinic (-111) plane and the monoclinic (111) plane ((-111) plane / (111) plane) of 0.50 to 0.95, and a polishing assistant.
10. A method for reducing surface roughness Ra, comprising polishing using zirconium oxide containing a monoclinic phase and having a crystallite size ratio between the monoclinic (-111) plane and the monoclinic (111) plane ((-111) plane / (111) plane) of 0.50 to 0.95, and a polishing aid.
11. A polishing powder comprising zirconium oxide powder containing a monoclinic phase and having a crystallite size ratio ((-111) / (111)) of 0.50 to 0.95 between the monoclinic (-111) plane and the monoclinic (111) plane.
12. The polishing powder according to claim 11, wherein the crystallite size of each crystal face of the zirconium oxide powder is 2.0 to 100.0 nm.
13. The polishing powder according to claim 11 or 12, wherein the zirconium oxide powder has an average secondary particle size of 0.002 to 5 μm.
14. The polishing powder according to claim 13, wherein the zirconium oxide particles have an average secondary particle size of 0.1 μm or less.
15. The polishing powder according to claim 11, wherein the purity of the zirconium oxide powder is 97% by mass or more.
16. The polishing powder according to claim 11, wherein the zirconium oxide powder is produced by a wet process.
17. The specific surface area of the zirconium oxide powder is 20 m 2 12. The polishing powder according to claim 11, wherein the abrasive grain size is 1 / g or more.
Citation Information
Patent Citations
Zirconium oxide particle and method for producing the same
JP2005170700A
Zirconia fine particle and method for producing the same
JP2010105892A
Polishing slurry containing zirconia particles and method for using the polishing slurry
JP2014504324A
Polishing composition, polishing method, and method of manufacturing semiconductor substrate
JP2023147178A